Stem cell and neurogenic gene-expression profiles link prostate basal cells to aggressive prostate cancer - Dingxiao Zhang (Nature Portfolio, 2016)
Gene-expression profiles can be used to predict the prognosis of cancer patients. Here, the authors describe gene expression profiles of human prostate epithelial lineages and show that basal cells have intrinsic stem and neurogenic properties, and molecularly resemble aggressive prostate cancer.